2021
DOI: 10.1177/1073191121998767
|View full text |Cite
|
Sign up to set email alerts
|

Wanting and Liking: Testing the Factor Structure of The Temporal Experience of Pleasure Scale in Major Depression and Community Samples

Abstract: The Temporal Experience of Pleasure Scale (TEPS) is a multidimensional self-report measure that has been used to improve understanding of anticipation (“wanting”) and consummation (“liking”) of reward. The TEPS has been used to assess anhedonia in clinical depression, but its factor structure has not yet been confirmed in this population. This seems important given mixed findings on the model fit and factor structure of the TEPS in other clinical and community samples. To remedy this, the current study used co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
3
5
0
Order By: Relevance
“…First, consistent with research findings differentiating between anticipatory and consummatory pleasure (e.g., Kringelbach & Berridge, 2009), our findings confirmed that the two-factor solution was the best fitting model for the TEPS. These findings echo past results with adults who also found support for the two-factor structure of the TEPS (e.g., Hallford & Austin, 2021), and suggest that contrary to concerns regarding the complex wording of items (Watson et al, 2020), the items were interpretable for adolescents. The present study also extends previous studies by demonstrating that the original two-factor model provides a better fit to the data than more complex (i.e., bifactor) models that are becoming increasingly popular approaches for measuring psychopathology risk and have relevance for conceptualizations of anhedonia (Olino et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…First, consistent with research findings differentiating between anticipatory and consummatory pleasure (e.g., Kringelbach & Berridge, 2009), our findings confirmed that the two-factor solution was the best fitting model for the TEPS. These findings echo past results with adults who also found support for the two-factor structure of the TEPS (e.g., Hallford & Austin, 2021), and suggest that contrary to concerns regarding the complex wording of items (Watson et al, 2020), the items were interpretable for adolescents. The present study also extends previous studies by demonstrating that the original two-factor model provides a better fit to the data than more complex (i.e., bifactor) models that are becoming increasingly popular approaches for measuring psychopathology risk and have relevance for conceptualizations of anhedonia (Olino et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…These findings provide insight into the percentage chance other factor solutions would emerge as providing the best fit if tested in another dataset. Additionally, following past research which suggested bifactor models to be relevant for conceptualizing anhedonia (Olino et al, 2018), as well as others who have reported the anticipatory and consummatory latent constructs to be highly correlated (e.g., Ho et al, 2015; Hallford & Austin, 2021), exploratory bifactor models using oblique Bi-Geomin rotation (Muthén & Muthén, 1998/2017) were tested to examine whether introducing a common factor would provide a more parsimonious solution in understanding the factor structure of the TEPS. Bifactor models with one general factor, and two, three, or four specific factors, were tested.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations